Midstream value creation in social marketing - Luca, Nadina Raluca; Hibbert, Sally; McDonald, Ruth (Taylor & Francis, 2016)
The purpose of this study is to develop improved understanding of how value is created at the midstream (meso) level in a collaborative smokefree homes and cars social marketing programme. The study adopts a qualitative approach including interviews and observation. The findings show that the co-creative organisational model adopted for the Smokefree programme affords access to resources and capabilities of midstream actors and provides opportunities for reshaping and mobilising existing value networks. The focal organisation has a key role in coordinating, connecting actors and providing resources to facilitate value co-creation at the network level. The study illustrates that the service interaction allowed for customer centred cues for action which took into account their context and the existence/lack of resources for value creation. The implications of this study are discussed, in particular in terms of the role of focal organisations in managing value networks, the social context, configurational fit and resources of actors involved in community based social marketing and the need for policies and practices to provide health professionals with role support for health promotion.